Lagrangian Dynamical Systems on Clifford Ka Ihler Manifolds (Global Journal of Science Frontier Research, 2017)
In his paper we obtained a canonical local basis { } , = 1,5 of vector bundle on Clifford ̈ℎ manifold (, ). The paths of semispray on Clifford ̈ℎ manifold are infact the solutions of Euler-Lagrange equations.
Keywords: vector bundle; paths of semispray; Euler-Lagrange equations